Adsorption and Release Properties of Drug Delivery System Naproxen-SBA-15: Effect of Surface Polarity, Sodium/Acid Drug Form and pH - Zauška, Ľuboš; Beňová, Eva; Urbanová, Martina; Brus, Jiří; Zeleňák, Vladimír; Hornebecq, Virginie; Almáši, Miroslav (Journal of functional biomaterials, 2022)
Mesoporous silica SBA-15 was prepared via sol-gel synthesis and functionalized with different types of organosilanes containing various organic functional groups: (3-aminopropyl)triethoxysilane (SBA-15-NH2), (3-mercaptopropyl)triethoxysilane (SBA-15-SH), triethoxymethylsilane (SBA-15-CH3), triethoxyphenylsilane (SBA-15-Ph), and (3-isocynatopropyl)triethoxysilane (SBA-15-NCO). The prepared materials were investigated as drug delivery systems for naproxen. As model drugs, naproxen acid (HNAP) and its sodium salt (NaNAP) were used. Mentioned medicaments belong to the group of non-steroidal anti-inflammatory drugs (NSAIDs). The prepared materials were characterized by different analytical methods such as transmission electron microscopy (TEM), infrared spectroscopy (IR), nitrogen adsorption/desorption analysis (N2), thermogravimetric analysis (TG), 1H, 13C and 23Na solid-state nuclear magnetic resonance spectroscopy (1H, 13C and 23Na ss-NMR). The abovementioned analytical techniques confirmed the successful grafting of functional groups to the SBA-15 surface and the adsorption of drugs after the impregnation process. The BET area values decreased from 927 m2 g-1 for SBA-15 to 408 m2 g-1 for SBA-15-NCO. After drug encapsulation, a more significant decrease in surface area was observed due to the filling of pores with drug molecules, while the most significant decrease was observed for the SBA-15-NH2 material (115 m2 g-1 for NaNAP and 101 m2 g-1 for HNAP). By combining TG and nitrogen adsorption results, the occurrence of functional groups and the affinity of drugs to the carriers' surface were calculated. The dominant factor was the volume of functional groups and intermolecular interactions. The highest drug affinity values were observed for phenyl and amine-modified materials (SBA-15-Ph = 1.379 μmol m-2 mmol-1 for NaNAP, 1.761 μmol m-2 mmol-1 for HNAP and SBA-15-NH2 = 1.343 μmol m-2 mmol-1 for NaNAP, 1.302 μmol m-2 mmol-1 for HNAP) due to the formation of hydrogen bonds and π-π interactions, respectively. Drug release properties and kinetic studies were performed at t = 37 °C (normal human body temperature) in different media with pH = 2 as simulated human gastric fluid and pH = 7.4, which simulated a physiological environment. Determination of drug release quantity was performed with UV-VIS spectroscopy. The surface polarity, pH and naproxen form influenced the total released amount of drug. In general, naproxen sodium salt has a higher solubility than its acid form, thus significantly affecting drug release from surface-modified SBA-15 materials. Different pH conditions involved surface protonation and formation/disruption of intermolecular interactions, influencing both the release rate and the total released amount of naproxen. Different kinetic models, zero-order, first-order, Higuchi and Hixson-Crowell models, were used to fit the drug release data. According to the obtained experimental results, the drug release rates and mechanisms were determined.
Keywords: polar and nonpolar functional groups; drug delivery system; pH; naproxen sodium/acid; surface modification; SBA-15